Makna dan Reduplikasi dalam Tembang Dolanan Jawa - Hamidah, Latifah Winda (Jurnal Bahasa dan Sastra, 2026)
One form of the culture is regional songs that are formed as a result of the social life of the local community. One of them is the tembang dolanan used to accompany certain games whose existence has diminished. This dolanan song consists of many lyrics that contain reduplication with a specific purpose such as affirming something. This study aims to describe the meaning and reduplication that found in the lyrics of the songs of Menthog-Menthog, Gajah-Gajah, Jaranan, Kancil, and Ula Sawah. This research method is qualitative using the method of collecting data by observing advanced note-taking techniques. The results of this study indicate that there are five reduplications in the five tembang dolanan, i.e., tembung dwilingga padha swara, tembung dwilingga salin swara, dwilingga semu, the dwipurwa tower, and tembung dwiwasana. Then the meaning of reduplication in the dolanan song found several meanings, i.e., many, repetitive activities, affirmations, and meaningless because it includes pseudo reduplication.